Study on failure of an ecological tunnel gate caused by jet-flow from air vents. (September 2017) - Qi, Huijun; Li, Tongchun; Liu, XiaoQing; Zhao, LanHao; Fan, ShuJie; Liu, Min
Abstract: This paper presents analysis of water jet flow state in an ecological tunnel in an abnormal condition and failure analysis of a temporary blocking gate of the ecological tunnel. Analysis consists of the determination of the hydrodynamic pressure on the gate by using experimental test and computational fluid dynamics, the calculation of stress distribution under different operating conditions using finite element method, and a simplified fatigue analysis. Results show that the water jet flow induces a vortex downstream the blocking gate, and under the large displacement and large dynamic stress the damage of gate begins with the local material failure and spreads to total damage with sandwich panel. Highlights: Determine the hydrodynamic pressure on the damaged gate Examine the impact of the panel material defect on the gate life Clarify the cause of the gate failure of a hydropower station